Toxic Metals Transfer from Heating Coils to e-liquids: Safety Assessment of Popular e-cigarettes in Jordan - Alhusban, Ala A.; Ata, Samah A.; Hamadneh, Lama A.; Tarawneh, Ola A.; Abuzaid, Haneen; Albustanji, Sokiyna; Awad, Mohammad K. (Jordan Journal of Pharmaceutical Sciences, 2023)
The rate of smokers in Jordan has been among the highest globally. Electronic Nicotine Delivery systems (ENDs) are considered helpful in smoking cessation but also have the potential for metals exposure resulting from their transfer from the metallic coils to the e-liquid upon use. Metal exposure is associated with severe health outcomes. We sought to assess the levels of toxic metals (Cr, Cd, Pb, Ni and Al) transfer from two of the most popular coils used in ENDs among users in Jordan. The validated inductively coupled plasma-optical emission spectroscopy (ICP-OES) with limit of detections (LODs) of 0.10, 0.90, 0.15, 0.13 and 1.00 mg.kg−1 was employed to measure the levels of toxic metals in the e-liquid samples. Following a repetitive usage of coils in both tank and pod systems for five continuous days, the cumulative amount of toxic metals; Ni, Cr, Al and Pb levels were significantly increased in all e-liquids used (p < 0.0001) compared to the fresh unheated samples. The obtained results showed a time-dependent increase of metals transfer from coils to e-liquids, thus highlighting the need for additional studies to re-assess the safety claims of using ENDs for smoking cessation.